CRITICAL THINKING AS AN EDUCATIONAL OBJECTIVE IN A GLOBAL INFORMATION SOCIETY - Mróz, Anna; Ocetkiewicz, Iwona; Walotek - Ściańska, Katarzyna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Critical thinking is defined as the competency for the future, which is crucial for every its member responsible participation in the global information society. Today, possessing this competence often determines how one perceives the reality and responds appropriately to the stimuli of the surrounding world. This competency should be shaped (created) by teachers, especially within the process of formal education. Teachers should choose specific methods and forms of work, the aim of which is to develop the components of the competency to think critically. The paper is a presentation of the results of research that aimed to examine the methods and forms of teachers' effort and work that create the critical thinking competency in students at the third (junior high school) and the fourth (high school) stages of education. Throughout the study, the authors sought an answer to the question: what methods and forms of education are used by teachers at the third and fourth stages of education to shape the critical thinking competency? The research was carried out using the quantitative approach. The research method was a survey and convenience sampling was used to select subjects. 337 Polish teachers participated in the study. The analysis of the results of the research suggests that Polish teachers are not sufficiently prepared to develop the critical thinking competency in their students. They lack methodological competencies at an appropriate level and are not even aware of the need for developing critical thinking in many cases.